Prevalence and gross pathology of liver fluke in macropods cohabiting livestock farms in north eastern NSW, Australia, and diagnosis using cELISA. (December 2021) - Lamb, Jane; Doyle, Emma; Barwick, Jamie; Chambers, Michael; Kahn, Lewis
Abstract: Liver fluke ( Fasciola hepatica ) is a parasite of herbivores including wildlife. Macropods, such as Eastern grey kangaroo ( Macropus giganteus ) and Common wallaroo ( Osphranter robustus ), are frequently observed sharing grazing sites with domestic livestock. The impact of Macropods, as reservoirs of infection, on livestock production and risks to cross-species transmission are largely unknown. In Phase 1 of this study, liver and faecal samples were collected from 245 Macropods (181 Eastern grey kangaroos, 64 Common wallaroos) cohabiting livestock farms (n = 7) in the Northern Tablelands regions of New South Wales. Total fluke (TFC) and fluke eggs (FEC) were counted in the liver and faeces, respectively, to assess prevalence. Faecal antigens were also measured using the commercial Bio-X Diagnostic Monoscreen AgELISA Fasciola hepatica kit (cELISA) to assess suitability as a diagnostic tool. In Phase 2, Macropod faecal samples were collected from 60 livestock farms to conduct FEC and assess prevalence by region. Liver fluke was prevalent in 22% of Eastern grey kangaroo and 20% of Common wallaroos with prevalence as high as 45% in the Eastern grey kangaroo. Fluke burdens ranged from 1 to 122 flukes (mean = 9 flukes) with a FEC range of 0–195 eggs per gram (epg) of faeces (mean = 18 epg). Evidence of dead and live flukes trapped within fibrotic capsules confirms the ability of Macropods to resolve infections. cELISA proved highly specific (100%) and sensitive (98%) in liver fluke detection however fibrotic capsules observed in the liver may reduce the correlation of coproantigens with fluke burden. Phase 2 revealed that 27% of livestock farms had Macropods infected with liver fluke. Overall, this study confirmed Eastern grey kangaroo and Common wallaroo are susceptible hosts and potential reservoirs for liver fluke and, monitoring infections in Macropods would assist in livestock disease management. Graphical abstract: Image 1 Highlights: Eastern grey kangaroo and Common wallaroo harbouring liver fluke in north eastern Australia. Macropods with liver fluke may limit effectiveness of integrated parasite management strategies for liver fluke control. Monitoring Macropod populations within liver fluke endemic regions may assist livestock disease management.